THROUGH THE USE OF DIGITAL GAME TECHNOLOGIES MECHANISMS FOR INCREASING COGNITIVE ACTIVITY - Bekmuratova, M.U.; Allanazarova, I.A. (SCIENCE and SOCIETY, 2026)
This article explores the field of game technologies and their role in strengthening student motivation in the digital educational environment. By incorporating game design elements such as points, badges, and awards, teachers can create interactive experiences that inspire students to actively engage with course materials. Gamification not only increases motivation but also improves learning outcomes by supporting diverse learning styles and developing critical thinking skills. The integration of game elements in the educational process allows for a radical improvement of teaching practice and prepares students for academic success in a constantly evolving technological environment.